New Records of Ditylenchus Species from Southern Alberta, Canada - Maria Munawar; Atta Ur Rahman; Pablo Castillo; Dmytro P. Yevtushenko (Plants, 2023)
The presence of plant-parasitic nematodes (PPNs) in cultivated areas is a limiting factor in achieving marketable crop yield. To control and alleviate the effects of these nematodes and determine appropriate management strategies, species-level identification is crucial. Therefore, we conducted a nematode diversity survey, which resulted in the detection of four Ditylenchus species in cultivated areas of southern Alberta, Canada. The recovered species had six lines in the lateral field, delicate stylets (>10 µm long), distinct postvulval uterine sacs, and pointed to rounded tail tips. The morphological and molecular characterization of these nematodes revealed their identity as D. anchilisposomus, D. clarus, D. tenuidens and D. valveus, all of which are members of the D. triformis group. All of the identified species were found to be new records in Canada except for D. valveus. Accurate Ditylenchus species identification is crucial because false-positive identification can result in the implementation of quarantine measures over the detected area. Our current study not only documented the presence of Ditylenchus species from southern Alberta, but also described their morpho-molecular characteristics and subsequent phylogenetic relationships with related species. The results of our study will aid in the decision on whether these species should become a part of nematode management programs since nontarget species can become pests due to changes in cropping patterns or climate.